Fazer o bem compensa? Uma reflexão sobre a responsabilidade social empresarial - Maria Alice Nunes Costa (Revista Crítica de Ciências Sociais, 2005)
This article presents an overview of current business management, or corporate social responsibility, developed since the 1990s. The author seeks to understand the political implications of this form of social solidarity in which economic agents intervene in the public space, promoting social welfare policies for low-income communities. The aim is to reflect on corporate social responsibility, not in an isolated manner, but taking into account a dynamic that involves an interface with the State and the community in the governance of contemporary social regulation.